The impact of financial defence mechanisms and phantasy on risky investment intention - Aren, Selim; Hamamci, Hatice Nayman (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose The purpose of this paper is to investigate the relationship between defence mechanisms, one of the unconscious processes, and phantasy. In addition, the scale of financial defence mechanisms, which is a version of the defence mechanisms adapted to financial issues, has been developed and tested. Design/methodology/approach For this purpose, first, a pilot study was conducted for the financial defence mechanism scale. The data was collected 179 subjects in Turkey through online surveys with convenience sampling method between the dates of 6 March and 21 March 2020, and then additional data was collected in Turkey between the dates of 28 April and 14 June 2020. The total number of subjects is 644. The authors exploited IBM SPSS Statistics and AMOS for analysis. Exploratory factor analysis, ANOVA, Independent t-test and Correlation analysis were performed. In addition, confirmatory factor analysis was performed after additional data collection process with structural equation modelling. Findings As a result of the analyses, only two of the defence mechanisms (mature and neurotic) and three of the financial defence mechanisms (mature, neurotic and immature) were found to be positively correlated with phantasy, which is considered a determinant of financial bubbles. In addition, a positive relationship was found between risky investment intention and two of the defence mechanisms (immature and neurotic) and three of the financial defence mechanisms (mature, immature and neurotic). Originality/value The study is unique due to its findings and developed scale. The findings are valuable in that the theoretically alleged relations were also obtained empirically.
Keywords: Defence mechanism; Financial defence mechanism; Phantasy; Risky investment intention; Emotional finance; STYLE QUESTIONNAIRE DSQ-40; HERD BEHAVIOR; PERSONALITY; VALIDITY; VERSION; DISORDER; SEX; AGE; Computer Science